A Need for Institutional Change to Manage Natural Disasters and Ecological Catastrophes - Bogomilova, Ekaterina (Research Papers, 2021)
In the last 20 years, the world has undergone significant changes with the increase not only in the natural processes related to climate change, but also in the challenges of adapting national policies and programs to the dynamic changes associated with natural disasters and environmental disasters. This dynamic requires a rethinking of the institutional framework, both in terms of organizational structures for managing these processes in the country, but also a change in social, economic and legislative initiative in response to these threats.